Residents’ sense of place and community cohesiveness on resilience towards insecurity situation in Maiduguri, Borno State, Nigeria - Butu, Hauwa Mai (2017)
The study was meant to determine residents’ sense of place and community cohesiveness on resilience towards insecurity situation in Maiduguri, Borno state, Nigeria. Place attachment theory by Bowlby (1969) and resilience theory by Kut Lewin, (1943) was adopted for the study. A 52-item questionnaire was administered on a sample size of 383 respondents using convenience sampling technique. Data acquired were analyzed using both descriptive and inferential statistics. The descriptive analysis of the socio-economic and the demographic variables indicated that 59% of the respondent were male while female were 41%, 80% of the respondents were aged between 18-50 years old. About 47% of the respondents were married and the mean score for a number of family members indicated that on the average households in Maiduguri have about 9 members. 64% of the respondents were Muslims and 60% of the respondents had tertiary education. In terms of occupation, 33% of whom are civil servants. On the average, the majority of the respondents have been in the area for 15 years. In terms of the level of resident’s resilience, it indicated that the residents have a moderate level of resilience. T-test was used to test for significant difference in mean between male and female based on gender and tenure. The results showed that there is a significant difference in the level of resilience based on gender, while tenure revealed no significant difference. More so the result of the ANOVA analysis revealed significance difference in the level of resilience based on marital status, while religion affiliation and occupation did not show any significant difference. Multiple regression analysis was used to investigate the impact of the sense of place, community cohesiveness and perception of insecurity on resilience. The regression analysis revealed that sense of place, community cohesiveness and perception of insecurity contributes significantly to residents’ resilience. The outcome from this research could provide policy maker with relevant information that can result in measures aimed at strategically rehabilitating affected residents and restructuring as well as developing neighbourhoods to prevent future occurrences.